Construction of Chiral Tetraorganosilicons by Tandem Desymmetrization of Silacyclobutanes/Intermolecular Dehydrogenative Silylation. Issue 4 (19th December 2016) - Zhang, Qing‐Wei; An, Kun; Liu, Li‐Chuan; Zhang, Qi; Guo, Huifang; He, Wei
Abstract: We report a method to construct chiral tetraorganosilicons by tandem silacyclobutane (SCB) desymmetrization–dehydrogenative silylations. A wide array of dibenzosiloles with stereogenic quaternary silicon centers were obtained in good yields and enantioselectivities up to 93 % ee . Chiral TMS‐segphos was found to be a superior ligand in terms of reactivity and enantioselectivity. Abstract : Chiral silicon : A Rh‐catalyzed reaction between silacyclobutane and (hetero)arenes in the presence of ( R )‐ or ( S )‐TMS‐segphos provides access to a wide array of chiral dibenzosiloles in good yields and enantioselectivities (up to 93 % ee ). The reaction proceeds through a rarely documented desymmetrization of silacyclobutane, followed by intra‐ and intermolecular dehydrogenative silylation processes.